Development and Preliminary Validation of the Youth Leadership Potential Scale - Yuan, Yue; Chen, Qing; Sun, Xiaomin; Liu, Zhenzhen; Xue, Gang; Yang, Di (Frontiers in Psychology, 2019)
To address the need for a valid and reliable scale of youth leadership potential based on the development theory of leadership, the current study developed the Youth Leadership Potential Scale (YLPS) and investigated its factor structure and psychometric properties in a sample of 696 students (grades 7-9) in China. Exploratory structural equation modeling (ESEM) identified a five-factor solution comprising leadership information, leadership attitude, communication skills, decision-making skills, and stress management skills. ESEM within confirmatory factor analysis demonstrated an adequate fit for this structure. The scale showed good composite reliability and measurement invariance across different gender and grade/age groups. The scale also showed sufficient concurrent validity with the Coping Self-Efficacy Scale, the Chinese Roets Rating Scale for Leadership, and the Leadership Skills Inventory. Furthermore, criterion-related validity was supported by the relationship between YLPS scores and the length of student leadership positions. The results suggest that the YLPS is a valid and pragmatic measure for assessing youth leadership potential. The current study is the first to develop a youth leadership potential scale based on the development theory of leadership.